La auditoría de gestión y su incidencia en la rotación de inventarios de la empresa Reybanpac c.l. Zona Fumisa, año 2022 - Loor Olivo, Sindy Vanessa (2024)
Management auditing is an essential tool in the modern business environment, used to evaluate and improve the internal processes of organizations. This study aims to evaluate the impact of the Management Audit on the Inventory rotation of the company Reybanpac C.L. Zona Fumisa, year 2022. High turnover is generally associated with efficient inventory management and is a critical factor in business management. The research corresponds to a descriptive and exploratory methodology, where deductive and inductive methods, analysis, synthesis were used, in addition, instruments were developed to apply to the different workers of the company, with questionnaires, audit exam guides, observation, interview and survey. ; As a result, in the inventory area there is a moderate level of confidence and a medium level of risk, the company does not have an internal inventory control manual, the staff is not familiar with the policies and there is a need for an action plan. to improve communication, functions and activities of all collaborators, in conclusion there is an orderly and systematic process, in the functions that are carried out in inventory the lack of technological tools predominates and a good space for sales volume is a fundamental factor in the procedures; and, the respective inventory control and its rotation, it is recommended to implement inventory control and rotation strategies in both the administrative and operational department, where the functions, values, policies and procedures must be emphasized to collaborators through training.